2023
DOI: 10.1186/s12912-023-01262-4
|View full text |Cite
|
Sign up to set email alerts
|

Communication competence, self-efficacy, and spiritual intelligence: evidence from nurses

Abstract: Introduction Communication skills and acceptable levels of spiritual intelligence (SI) are the prerequisites of the nursing profession, which can significantly impact the individual and organizational performance of nurses. This study aimed to investigate the competency and self-efficacy of communication and its relationship with the SI of nurses. Methods This cross-sectional study was conducted in 2021 and included 312 nurses working in a COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Lim et al in their study indicated that signifcantly nurses aged 50 years or more have high self-efcacy [10]. Also, Mehralian et al in their study on 312 nurses working in a COVID-19 hospital in the south of Iran; they also reached a similar conclusion [29]. Terefore, it can be concluded that age is one of the important factors in nurses' self-efcacy against COVID-19.…”
Section: Comparison Between Csec and Jsc Scores Amongmentioning
confidence: 79%
“…Lim et al in their study indicated that signifcantly nurses aged 50 years or more have high self-efcacy [10]. Also, Mehralian et al in their study on 312 nurses working in a COVID-19 hospital in the south of Iran; they also reached a similar conclusion [29]. Terefore, it can be concluded that age is one of the important factors in nurses' self-efcacy against COVID-19.…”
Section: Comparison Between Csec and Jsc Scores Amongmentioning
confidence: 79%
“…Furthermore, communication competence and the ability to establish effective communication improve nurse performance. awareness of patient issues and concerns (Hemberg & Vilander, 2017), improve decisions about patient discharge and transfer (Bullington et al, 2019), provide appropriate healthcare solutions, and promote quality patient care (Karabuga Yakar & Ecevit Alpar, 2018), increasing the sense of participation and cooperation in the care team, increasing skills, knowledge, and attitudes, reducing medication errors (Soares et al, 2021), reducing the length of stay in the hospital (Allenbaugh et al, 2019), reducing treatment costs, reducing stress and job burnout, increase productivity and satisfaction, and promote job performance (Mehralian et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…There have been few studies that have reported on self-efficacy in nurses and their willingness to provide spiritual care. Recent researches support that nurses with higher levels of self-efficacy tend to perceive themselves as more competent in providing spiritual care [ 9 , 22 ]. Furthermore, the introduction of a training course focused on spiritual care had a significant impact on nursing students’ self-efficacy in providing spiritual care [ 10 ].…”
Section: Discussionmentioning
confidence: 99%